Fun, influence and competence-a mixed methods study of prerequisites for high school students' participation in physical education - Eirik Abildsnes; Gudrun Rohde; Sveinung Berntsen; Tonje H. Stea (BMC, 2017)
Abstract Background Many adolescents do not reach the recommended levels of physical activity (PA), and students attending vocational studies are less committed to take part in physical education (PE) than other students. The purpose of the present study was twofold: 1) to examine differences in physical activity, diet, smoking habits, sleep and screen time among Norwegian vocational high school students who selected either a PE model focusing on PA skills, technique and improvement of physical performance ("Sports enjoyment") or more on health, play and having fun when participating in PE lessons ("Motion enjoyment"), and 2) to explore the students' experiences with PE programs. Methods In this mixed methods study 181 out of 220 invited students (82%) comprising 141 (78%) girls and 40 (22%) boys attending vocational studies of Restaurant and Food Processing (24%), Design, Arts and Crafts (27%) or Healthcare, Childhood and Youth Development (49%) were recruited for participation in the new PE program. PA level, sedentary time and sleep were objectively recorded using the SenseWear Armband Mini. A self-report questionnaire was used to assess dietary habits, smoking and snuffing habits, use of alcohol, screen use and active transportation. Four focus group interviews with 23 students (12 boys) were conducted to explore how the students experienced the new PE program. Results Students attending "Motion enjoyment" accrued less steps/day compared to the "Sports enjoyment" group (6661 (5514, 7808) vs.9167 (7945, 10390) steps/day) and reported higher screen use (mean, 3.1; 95% CI, 2.8, 3.5) vs. 2.4 (2.0, 2.9) hours/day). Compared to those attending "Sports enjoyment", a higher number of students attending "Motion enjoyment" reported an irregular meal pattern (adjusted odds ratio, 5.40; 95% confidence interval (CI), 2.28, 12.78), and being a current smoker (12.22 (1.62, 107.95)). The students participating in the focus group interviews emphasized the importance of having competent and engaging teachers, being able to influence the content of the PE program themselves, and that PE classes should include a variety of fun activities. Conclusion Students selecting "Motion enjoyment" accrued less steps/day and reported overall more unhealthy lifestyle habits, including higher screen time, a more irregular meal pattern and a higher number were current smokers, compared to those selecting "Sports enjoyment". Program evaluation revealed that both groups of students valued competent PE teachers and having influence on the content of the PE program.